PREVALENCE OF ISOSPORA SPP. INFECTION IN CATS IN DENPASAR CITY - Mesquita, Nelviana; Suratma, Nyoman Adi; Dwinata, I Made (Buletin Veteriner Udayana, 2022)
Cats are one of the most popular pets in the world with a wide variety of breeds, and as pets that get attention to be kept and bred.The common gastrointestinal protozoa that infect cats are  Gardia felis, Cryptosporidium felis, Isospora felis, Isospora rivolta, Toxoplasma gondii, Hammondia hammondi  and  Sarcocystis sp ., while  Pentatrichomonas hominis  can infect the large intestine. This study aims to determine the prevalence of infection and the relationship between some factors (breed, sex, age, and maintenance management) on gastrointestinal protozoa in cats in Denpasar. This study involved 100 samples of cat feces and the data were analyzed by chi-square. Samples were examined using the floating concentration method, with a saturated NaCl flotation agent. The results showed that the prevalence of gastrointestinal protozoa infections in cats reached 24% (24/100). Breed, sex, age and maintenance management factors were not associated with the prevalence of gastrointestinal protozoa infections in cats.